Effect of Nanosized TiC0.37N0.63 on Unlubricated Wear Responses of Si3N‐Based Nanocomposites Under Low Hertzian Stress. Issue 3 (25th November 2015) - Lee, Alex Chinghuan; Lu, Horng‐Hwa; Goto, Takashi; Tu, Rong; Lin, Hua‐Tay; Lii, Ding‐Fu; Nayak, Pramoda K.; Huang, Jow‐Lay
Abstract : Si3 N4 ‐based nanocomposites containing 0–50 wt% TiC0.37 N0.63 are directly consolidated at 1700°C by spark plasma sintering, and their reciprocal sliding behavior against a Si3 N4 counterbody is investigated under a maximum Hertzian stress of 1.27 GPa in unlubricated conditions. The average grain widths of Si3 N4 and TiC0.37 N0.63 are about 85 and 90 nm, respectively. The decreasing relative densities of the as‐sintered nanocomposites indicate that the nano‐TiC0.37 N0.63 may introduce pores and reduce the hardness and fracture resistance of the materials. The brittleness index for sliding contacts in all the samples is 25–31, indicating brittle fracture taking place on the wear surface and inducing cavities. When the mean free paths of nano‐TiC0.37 N0.63 are slightly greater than grain length of Si3 N4, the best wear resistance is achieved in Si3 N4 containing 20/30 wt% TiC0.37 N0.63 due to the process of surface smoothing by triboproducts. Severe wear response can be observed in Si3 N4 nanocomposites containing 0, 10, 40, and 50 wt% of TiC0.37 N0.63 . The wear responses are explained by considering the microstructural parameters (like grain characteristics for both phases and mean free path of nano‐TiC0.37 N0.63 ) and contact‐induced fracturing behavior, as well as tribochemical reactions.